Weather Index Insurance for Agriculture : Guidance for Development Practitioners - World Bank (World Bank, Washington, DC, 2017)
This paper is a distillation of the findings of the work undertaken by the World Bank. It is deliberately not a collation of case studies, but rather a practical overview of the subject. The purpose of this paper is to introduce task managers and development professionals, who are not insurance sector specialists, to weather index insurance. Ultimately, the paper seeks to take the reader through the main decision points that would lead to a decision to embark upon a weather index insurance pilot and then assists them to understand the technical procedures and requirements that are involved with it. In addition, the paper seeks to advise the reader of the practical challenges and implications that are involved with a pilot of this nature and what they might expect to encounter during the initial stages of implementation. The very nature of an index based product creates the chance that an insured party may not be paid when they suffer loss and/or that they may receive a payment when they have suffered no loss. This paper also does not seek to delve deeply into the technical details and science that lie behind the 'black box' that is at the heart of the index.